The origin of the electron distribution in SnO - WATSON, GRAEME WILLIAM (My University, 2001)
The origin of the electron distribution in SnO Graeme W. Watson Department of Chemistry, Trinity College, Dublin 2, Ireland ~ Received 12 September 2000; accepted 17 October 2000 ! Gradient corrected density functional theory calculations have been performed on SnO in the litharge and idealized CsCl structures with the litharge structure in good agreement with experiment. The CsCl structured SnO has a spherical electron density whereas the litharge structured SnO has a nonspherical electron distribution. Such asymmetry is often attributed to a sterically active lone pair formed by the 5 s 2 electrons which does not take part in chemical bonding. However, analysis of the density of states and band structures indicates that the situation is more complicated. In CsCl structured SnO mixing of the Sn 5 s with the oxygen 2 p electronic states results in filled bonding and antibonding combinations. The antibonding combinations, at the top of valence band, can interact with Sn 5 p to stabilize the structure, only when in the distorted litharge structure resulting in the asymmetric electron density. This is in contrast to the classical theory of hybridization of the tin 5 s and 5 p orbitals to form a ``lone pair?? as the asymmetric electron distribution is the result of the tin?oxygen covalent interactions.
PUBLISHED
Keywords: ``lone pair??; ``lone pair??